Underworld. Rise of the Lycans [videorecording (DVD)] - Wiseman, Len; Grevioux, Kevin (Sony Pictures Home Entertainment, 2009)
Traces the origins of the centuries-old blood feud between the aristocratic vampires and their onetime slaves, the Lycans. In the Dark Ages, Lucian is a young Lycan who emerges as a powerful leader who rallies the werewolves to rise up against Viktor, the cruel vampire king who has enslaved them. Lucian is joined by his secret lover, Sonja, whose the daughter of Viktor, in his battle against the Vampire army and his struggle for Lycan freedom.